Microbial treatment performance with developed bioconversion process for citric acid production from sewage treatment plant sludge - Jamal, Parveen; Alam, Md. Zahangir; Mohamed Salleh, Mohamad Ramlan; M. Akib, Munirah (2005)
In Malaysia, Sewage Treatment Plant Sludge (STP sludge) is the largest contributor of organic pollution to water resources and soil. Its contribution is top listed (64.4%), followed by animal husbandry wastes (32.2%), agro based pollutants (1.7%) and industrial effluents (1.3%) in terms of BOD load. In this study, STP sludge was used as substrate because it is an inexpensive and easily available raw material and a good source for growth of microorganisms due to enough nutrients and trace elements present for citric acid production with optimum process conditions. Citric acid is one of the important chemicals used in various industrial processes. It is estimated that about 500,000 tons of citric acid is produced annually by fermentation of expensive raw materials like glucose and sucrose. The optimum process factors determined by central composite design (CCD) using the statistical software MINITAB from previous study were: substrate concentration of 1%; both wheat flour and glucose concentrations of 4%; fermentation period of 6 days with absence of ammonium nitrate. The strain Aspergillus niger (A-SS106), isolated and screened by another work, was used throughout the study. Evaluation of the treatment performance was done in terms of maximum citric acid production, biosolids accumulation, chemical oxygen demand (COD) removal and reduction of reducing sugar. The maximum citric acid production was 1.296 g/l on 6th day at pH 1.57 with the reduction of COD concentration from 82.5 g/l to 22.6 g/l. Reducing sugar showed a decreasing trend from the beginning but maximum decrease was observed on the last two days of the fermentation process.